2009
DOI: 10.2147/ppa.s6351
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and determinants of patient satisfaction in oncology: A review of the literature

Abstract: Abstract:Cancer is one of the leading causes of morbidity and mortality in the United States. It places considerable mental, physical, and emotional stress on patients and requires them to make major adjustments in many key areas of their lives. As a consequence, the demands on health care providers to satisfy the complex care needs of cancer patients increase manifold. Of late, patient satisfaction has been recognized as one of the key indicators of health care quality and is now being used by health care ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 61 publications
(79 reference statements)
1
26
0
2
Order By: Relevance
“…Th e research revealed that there was little consistency in the eff ect of age on satisfaction with care 10 . Pini et al 16 found no statistically signifi cant relationship of overall satisfaction with demographics and other factors, although grading of services seemed to be aff ected by the patient health status, education and sex.…”
Section: Sociodemographic and Hospital-related Featuresmentioning
confidence: 97%
See 2 more Smart Citations
“…Th e research revealed that there was little consistency in the eff ect of age on satisfaction with care 10 . Pini et al 16 found no statistically signifi cant relationship of overall satisfaction with demographics and other factors, although grading of services seemed to be aff ected by the patient health status, education and sex.…”
Section: Sociodemographic and Hospital-related Featuresmentioning
confidence: 97%
“…It is well known that cancer diagnosis places considerable mental, physical, and emotional stress on patients and requires them to make major adjustments in many key areas of their lives 10 . Cancer patients are at a high risk of a variety of emotional disorders including anxiety, traumatic stress, and depression [11][12][13] .…”
Section: Psychological Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a double problem. First, waiting time is a factor of patient dissatisfaction (Lis, Rodeghier, and Gupta 2009). Second, patients who are waiting consume resources.…”
Section: Setting and Care Processmentioning
confidence: 99%
“…(7,8) Hasta memnuniyeti, hastaların yalnızca gerekli bakım ve tedaviyi gördüklerini hissetmeleri ile ilgili olmayıp aynı zamanda hastane ortamı ve sağlanan bakımın kalitesinden memnun olmalarıyla da ilgili bir durumdur. (9) Hastaların, gelecekteki başka sağlık sorunlarıyla geri dönme eğiliminde olmaları ve diğer hastalara tavsiye etme olasılıkları nedeniyle kurumların eksikliklerini belirleyerek bu eksikliklerin giderilmesinde, hasta memnuniyetinin ve hizmet kalitesinin değerlendirilmesinin yol gösterici olabileceğini göz önünde tutması gerekmektedir. (7,10) Çünkü hastanın, algıladığı kalite ile beklediği kalite arasında karşılaştırma yaparak edindiği sonuç onun memnuniyetini ortaya çıkarır.…”
unclassified